Enhancing oral health for better mental health: Exploring the views of mental health professionals. (27th March 2017) - Scrine, Clair; Durey, Angela; Slack‐Smith, Linda
Abstract: The association between oral health, self‐esteem and quality of life is well established yet there is limited research on the impact of addressing the poor oral health of people living with mental health disorders. Greater consideration is warranted on how enhancing oral health in the course of mental healthcare might reduce the burden of a person's ill health. The role of mental health professionals is important in this regard yet uncertainty persists about the role these providers can and should play in promoting oral health care for people with mental health disorders. This qualitative study explored the issue of oral health and mental health with community based mental health professionals in Perth, Western Australia. It examined their views on the oral health status and experiences of their clients, and the different and alternative ways to improve access to care, knowledge and preventative regimens. Findings indicated participants' ambivalence, reluctance and lack of training in raising oral health issues, despite its acknowledged importance, indicating a siloed approach to care. Findings offer an opportunity to reflect on whether a more integrated approach to oral health care for people with mental health disorders would improve health outcomes.